An integrated understanding of the physiological response to elevated extracellular phosphate1. Issue 7 (21st March 2013) - Camalier, Corinne E.; Yi, Ming; Yu, Li‐Rong; Hood, Brian L.; Conrads, Kelly A.; Lee, Young Jae; Lin, Yiming; Garneys, Laura M.; Bouloux, Gary F.; Young, Matthew R.; Veenstra, Timothy D.; Stephens, Robert M.; et al.
Abstract Recent studies have suggested that changes in serum phosphate levels influence pathological states associated with aging such as cancer, bone metabolism, and cardiovascular function, even in individuals with normal renal function. The causes are only beginning to be elucidated but are likely a combination of endocrine, paracrine, autocrine, and cell autonomous effects. We have used an integrated quantitative biology approach, combining transcriptomics and proteomics to define a multi‐phase, extracellular phosphate‐induced, signaling network in pre‐osteoblasts as well as primary human and mouse mesenchymal stromal cells. We identified a rapid mitogenic response stimulated by elevated phosphate that results in the induction of immediate early genes including c‐fos. The mechanism of activation requires FGF receptor signaling followed by stimulation of N‐Ras and activation of AP‐1 and serum response elements. A distinct long‐term response also requires FGF receptor signaling and results in N‐Ras activation and expression of genes and secretion of proteins involved in matrix regulation, calcification, and angiogenesis. The late response is synergistically enhanced by addition of FGF23 peptide. The intermediate phase results in increased oxidative phosphorylation and ATP production and is necessary for the late response providing a functional link between the phases. Collectively, the results define elevated phosphate, as a mitogen and define specific mechanisms by which phosphate stimulates proliferation and matrix regulation. Our approach provides a comprehensive understanding of the cellular response to elevated extracellular phosphate, functionally connecting temporally coordinated signaling, transcriptional, and metabolic events with changes in long‐term cell behavior. J. Cell. Physiol. 228: 1536–1550, 2013. © 2012 Wiley Periodicals, Inc.